2020
DOI: 10.1007/s42106-020-00088-3
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Biochemical Responses of Forage Grass Varieties to Mild Drought Stress Under Field Conditions

Abstract: In view of the expected increase in drought periods, researchers and breeders are searching for forage grasses that are more tolerant to drought stress. This study wanted to examine the physiological and biochemical reactions of nine forage grass varieties belonging to Festuca, Lolium and Festulolium under mild drought stress conditions in a semi-controlled field experiment. A mild drought stress treatment was applied in the period between cut II and cut III using three large mobile rain-out shelters equipped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 53 publications
14
28
0
Order By: Relevance
“…This condition might be related to the average height of germplasm of 118 vs 79 cm during rainy and dry seasons, respectively. Therefore, growth in height could result from the leaf material reduction and respective digestibility (Kalmbacher et al 1980), and possibly the drought stress may delaying maturity which can improved organic matter digestibility of forages (Fariaszewska et al, 2020). The correlations found in the M. maximus collection were similar to those reported by Stabile et al (2010) with commercial cultivars.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…This condition might be related to the average height of germplasm of 118 vs 79 cm during rainy and dry seasons, respectively. Therefore, growth in height could result from the leaf material reduction and respective digestibility (Kalmbacher et al 1980), and possibly the drought stress may delaying maturity which can improved organic matter digestibility of forages (Fariaszewska et al, 2020). The correlations found in the M. maximus collection were similar to those reported by Stabile et al (2010) with commercial cultivars.…”
Section: Discussionsupporting
confidence: 62%
“…In tropical regions of Colombia, there are productive differences between commercial cultivars, which could be associated with aspects inherent to morphology (Patiño et al, 2018) and nutritional pro le, these are advantageous characteristics in terms of adaptation to different livestock systems Some studies suggest that in vitro and in vivo digestibility of organic matter increases with rainy seasons (Vargas et al, 2013 andSilva TVS et al, 2017) and others show that water stress did not signi cantly affect the digestibility of organic matter (OMD) (Fariaszewska et al, 2020). The ndings in this research found ADF decreased and IVDMD slightly increased during the dry season compared to the rainy season.…”
Section: Discussionmentioning
confidence: 99%
“…Under summer establishment, the Drought condition reduced stem diameter and AGB in all treatments except for the Conv treatment. Fariaszewska et al (2020) found that AGB for Festuca, Lolium and Festulolium decreased following a period of drought, which concurs with the present study, where all the treatments containing Festulolium had a lower AGB under drought conditions. However, Conv, a mixture of Festuca rubra and Lolium perenne, did not conform to the findings of Fariaszewska et al (2020).…”
Section: Plant Trait Scores Related To Soil Erosion Control In Gwwssupporting
confidence: 93%
“…At T2, soil water availability was not yet limiting (83% REW, Figure 2), but VPD was high (3.06 kPa, versus 2.51 kPa at T1) ( Table 1), suggesting that Lp has a more strict stomatal regulation to atmospheric conditions than Fa. This confirmed other studies that reported larger stomatal conductance values of Fa under control conditions [15] and stomatal closure occurring at lower (i.e., more negative) leaf water potential than Lp [86,87]. These differences in stomatal control can be caused by several mechanisms.…”
Section: Research Question 4: Distinct Behaviour Within and Between Tsupporting
confidence: 90%
“…In addition, tetraploid varieties have a more open sward and are less persistent [12]. Although Festuca arundinacea (Fa) has a lower feeding quality than Lp, its yield potential is larger, especially under drought conditions, owing to its deeper rooting [13][14][15].…”
Section: Introductionmentioning
confidence: 99%